The Use of Nata de Coco Derived Bacterial Cellulose as a Potential Excipient for Directly Compressed Tablets - Sahudin, Shariza; Hussain, Mumtaz; Abd Rahman, Shaharizuan; Shahkirin Hamdan, Muhammad Aliff; Abd Rahim, Muhamad Rizal (International Pharmacy Acta, 2020)
Introduction: Nata de coco is produced through the fermentation of coconut water using Acetobacter xylinum bacteria. Nata de coco is chemically high in fiber, consisting of bacteria-derived cellulose. Bacterial celluloses present a number of unique physical properties compared to plant celluloses including a relatively high purity and crystallinity, with mechanical strength. These properties lend Nata de coco to be extremely amenable to research. Methods and Results: The current study attempts to assess the suitability of Nata de Coco derived bacterial cellulose in direct compression tablet formulation. Nata de coco, at various states of hydration, defined here as 0%, ‘low’ and ‘high’, achieved by both oven-drying and freeze-drying is incorporated into a low-dose loratadine powder blend for direct compression into tablets. The dissolution profile of these novel tablets was evaluated for release properties. The resulting tablets reveal freeze-drying, compared with oven-drying, markedly improve the properties of Nata de Coco for inclusion in a tablet formulation, producing tablets with improved disintegration times and dissolution profiles and retaining physical stability. Ovendried Nata de Coco, resulting in physically weaker tablets, with poor friability and hardness. The upper limit for water-content in both cases, similar to HPMC, appears to be 11%. Conclusions: Freeze-dried Nata de Coco, therefore presents considerable promise for use as a tablet excipient to produce a rapid-release formulation.